2018
DOI: 10.1039/c8ta05593a
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the performance of perovskite solar cells through a novel active passivation method

Abstract: Potassium halides have recently garnered much attention, due to their improvement of perovskite solar cell performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…Recently, high performing perovskite devices have increased compositional complexity by incorporating Group 1 (alkali metals) elements such as Na, K, or Cs. These materials have also been adopted as a dopant or an additional layer on ETLs for alleviating trap states at the ETL/perovskite interface . Seo et al reported a modification of the TiO 2 surface by CsBr to strengthen its interaction with the perovskite for rapid extraction of photogenerated electrons which lead to very high fill factor close to 80% from their cells.…”
Section: Passivation Of Carrier Transport Layer (Ctl)mentioning
confidence: 99%
“…Recently, high performing perovskite devices have increased compositional complexity by incorporating Group 1 (alkali metals) elements such as Na, K, or Cs. These materials have also been adopted as a dopant or an additional layer on ETLs for alleviating trap states at the ETL/perovskite interface . Seo et al reported a modification of the TiO 2 surface by CsBr to strengthen its interaction with the perovskite for rapid extraction of photogenerated electrons which lead to very high fill factor close to 80% from their cells.…”
Section: Passivation Of Carrier Transport Layer (Ctl)mentioning
confidence: 99%
“…The KCl‐passivated method is conducive to the enhancement of perovskite crystallinity and light absorption capacity and the reduction of defect states. [ 70 ] In addition, Huang et al proposed a strategy for effective surface passivation of blade‐coated perovskite films using cadmium iodide (CdI 2 )‐coating treatment shown in Figure 4c. Cd 2+ can replace part of Pb 2+ to inhibit the formation of halide vacancy due to the stronger CdI bond energy.…”
Section: Various Types Of Defectsmentioning
confidence: 99%
“…Reproduced with permission. [ 70 ] Copyright 2018, Royal Society of Chemistry. c) Schematic illustration of blade‐coated perovskite film with CdI 2 surface treatment.…”
Section: Various Types Of Defectsmentioning
confidence: 99%
“…With respect to the latter, several studies have shown alkali metals (Li, Na, K, Rb, and Cs) introduced as additives in the perovskite precursor solution to increase device performance and reduce hysteresis . Very few studies have introduced these alkali metal salts directly to the interface, where defects predominantly reside.…”
Section: Introductionmentioning
confidence: 99%